THE EFFECT OF PLANT DISTANCE IN INTERCROPPING PATTERN AND FERTILIZATION ON THE PRODUCTION OF CASAVA (Manihot esculenta Crantz) VARIETY OF ELEPHANT IN SIKKA DISTRICT - Yovita Yasintha Bolly (Jurnal Ecosolum, 2021)
Cassava (Manihot esculenta Crantz) is a local food that has long been cultivated and consumed by almost all people in Sikka Regency. In cultivating cassava, farmers generally still use traditional techniques so that it has not had an impact on increasing cassava production. Cassava production can be improved through several efforts, namely using superior varieties, setting planting distance, and fertilizing activities according to plant needs. This study aimed to determine the effect of planting distance and types of inorganic fertilizers on cassava production in the Sikka Regency. This research was designed using a factorial randomized block design, namely planting distance (T) and type of fertilizer (P). Each factor consists of several levels that combine six treatments, including T2P0, T2P1, T2P2, T3P0, T3P1, and T3P2. Each treatment was repeated three times to obtain 18 experimental units. Observation variables include the number of tubers per plant and tuber wet weight per plant. Observation data were analyzed using analysis of variance (ANOVA). The results showed that the addition of Urea, SP36, and NPK Phonska (complete) fertilizers could increase the wet weight of cassava at a planting distance of 2x1 m. and the planting distance of 2x1 m had a significant effect on the number of tubers/plant, and at the planting distance of 1x1 m supported by fertilization was able to increase the wet weight of tubers/plants.